E-gaming: an active learning pedagogy for engaging learners in a private university in Karachi, Pakistan - Laila Akber Cassum; Fatima, Syeda Sadia (Journal of the Pakistan Medical Association, 2024)
There is a radical shift in teaching and learning pedagogies to engage the learners in healthcare profession. It was a tough challenge for Pakistani educators of an esteemed university to motivate and assess the learners for concept absorption and critical reasoning using creative approaches. Teaching and learning styles have changed fundamentally from conventional teacher centred to inquiry-based student-centred approach. Classroom teaching in recognised nursing and medical institutes in Pakistan have transformed to blended and entirely online methodologies with the integration of diverse active learning strategies. The educators grapple to engage the millennials and to encounter this, gaming technological platform was used to facilitate the learners for maximum integration, active participation, and create an exciting learning experience. Various e-gaming tools, such as Kahoot, Jamboard, Padlet Wall, Ed-Puzzle, Mentimeter, etc., were used in nursing and medical courses and were highly appreciated by the leaners to retain, review, and self-assess.